Simulation and Modelling of Switching High-Voltage Power Supply; Chemical Engineering Transactions; Vol. 70 - Kalinchuk V. I. Vladislav Ivanovich; Zhuravlyov A. M. Artyom Mikhaylovich; Goryunov A. G. Aleksey Germanovich; Khasenova I. Zh. Indira Zhensbekovna (2018, 2018)
Title screen